Associations between polypharmacy and physical performance measures in older adults. (January 2022) - Ozkok, Serdar; Aydin, Caglar Ozer; Sacar, Duygu Erbas; Catikkas, Nezahat Muge; Erdogan, Tugba; Kilic, Cihan; Karan, Mehmet Akif; Bahat, Gulistan
Highlights: Patients with polypharmacy (≥ 5 medications) demonstrated poorer physical performance. Polypharmacy was significantly associated with slow gait speed in regression model consisted of age, sex and body mass index. The relationship disappeared after inclusion of comorbidities in the first model; suggested that participants might be slow walkers due to their chronic diseases. Polypharmacy was independently associated with poor SPPB and CSST performance in both models. Relationship between polypharmacy and falls, fractures and disabilities might be explained by its association with poor physical performance. Abstract: Objectives: A preserved ambulation is one of the keypoints for functionality and polypharmacy, a common problem in older adults, is associated with worse functional status. Our aim was to examine the associations of polypharmacy with certain physical performance measures used to evaluate ambulation. Methods: This retrospective, cross-sectional study was conducted in a geriatric outpatient clinic. Using ≥5 medications was accepted as polypharmacy. Usual gait speed (UGS), chair sit-to-stand test (CSST), timed up and go test (TUG) and short physical performance battery (SPPB) were performed to assess physical performance status. We created two models for logistic regression analyses: Model 1 was adjusted for age, sex and body mass index (BMI). We added comorbidities to Model 1 and further created Model 2. Results: There were 392 participants (69.1% were female, mean age: 73.9±6.2 years). Polypharmacy was seen in 62.5%. Participants with polypharmacy presented with a poor physical performance compared to the no-polypharmacy group (p<0.001, for each). In multivariate analyses, polypharmacy was independently associated with poor SPPB ( Odds Ratio (OR)=2.5; 95% Confidence Interval (CI)=1.3-4.7 and OR=2.4; 95% CI=1.2-4.8 for Model 1 and 2, respectively) and long CSST ( OR= 2.6; 95% CI=1.3-5.2 and OR=3.7; 95% CI=1.7-8.2 for Model 1 and 2, respectively). There was a significant association between polypharmacy and slow UGS in Model 1 ( OR=1.9; 95% CI=1.0-3.5 ); but relationship did not persist after adding comorbidities into the first model ( OR=1.6; 95% CI= 0.8-3.1 ). There was no significant association between long TUG and polypharmacy in any of the models. Conclusion: Polypharmacy is well-known with its association with falls and fractures in older adults and this might be explained by its association with poor physical performance. Whether polypharmacy causes a deterioration in physical performance is an issue needs to be enlightened by further longitudinal studies. Graphical abstract: Image, graphical abstract